Spectrum of dentofacial deformities: a retrospective survey. - Ong, M.A.H. (2004)
The findings suggest that the majority of the patients are young adult female students with skeletal class III pattern and treated for mandibular prognathism. The complication of persistent numbness and higher rate of postoperative infection indicate that longterm reviews and good antibiotic prophylaxis/therapy are necessary.